DESIGN STUDY OF Pb-Bi COOLED FAST REACTOR WITH NATURAL THORIUM AND URANIUM AS FUEL CYCLE INPUT - FAKHRUDDIN (NIM : 10205071 ); Pembimbing : Prof. Dr.Eng. Zaki SuÃ‚Â’ud, FAHMI
Design study of Lead-cooled fast reactor for small and medium core size to optimize fuel utilization, and to optimize inherent safety of the reactor has been done. The reactors utilize UN-PuN as fuel and lead-bismuth as coolant. These reactors operate at power 600 MWth with cylindrical geometry and 10 years reactor operation without refueling. The optimization evaluate by using SRAC code with two-dimensional core model (R-Z) Reactor design optimization is evaluated to utilize natural uranium. Optimization evaluated by divide the core into 10 axial region. After 10 years reactor operation, the first region will be shifted by the second region and continously until the tenth region. The first region will be fulfill by the fresh fuel. Fuel region consist 6,25% thorium nitride fuel and 93,75% uranium nitride. This reactor is constructed with 350 cm height and 240 cm cillinder diameter with power level 600 MWth, this reactor has the volume fraction is 65% of fuel, 10% of cladding and 25% of coolant.